Pain in the Emergency Department with One-Week Follow-Up of Pain Resolution - C Celeste Johnston; Anita J Gagnon; Carolyn J Pepler; Patricia Bourgault (Pain Research and Management, 2005)
OBJECTIVES: To determine the intensity of pain in the emergency department (ED), the use of analgesics in relation to pain intensity, which patients are at risk for unresolved pain at one week post-discharge, and the postdischarge treatment of pain.